Intrapleural Administration With Rh-Endostatin and Chemical Irritants in the Control of Malignant Pleural Effusion: A Systematic Review and Meta-Analysis - Wang, Cheng-Qiong; Huang, Xiao-Rong; He, Min; Zheng, Xiao-Tian; Jiang, Hong; Chen, Qian; Fan, Teng-Yan; Zhan, Lin; Ling, Juan; Feng, Ji-Hong; Xiao, Xue; Chen, Xiao-Fan; et al. (Frontiers in Oncology, 2021)
Introduction A modified and recombinant human endostatin (Rh-endostatin) is often used in the control of malignant pleural effusion (MPE) through intrapleural infusion. Objectives To demonstrate the clinical response, survival, and safety of Rh-endostatin plus chemical irritants, their optimal combinations, treatment threshold, and optimal usage, we performed a new systematic review and meta-analysis. Methodology All randomized controlled trials (RCTs) were collected from Chinese and English electronic databases (from inception until August 2020). We pooled the data using a series of meta-analyses and summarized the evidence quality following the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Results We included 75 RCTs recruiting 4,678 patients, which reported six combinations for Rh-endostatin plus chemical irritants. Among the six combinations, only Rh-endostatin plus cisplatin (DDP) with enough trials might improve the complete response [2.29 (1.93, 2.71)] and quality of life [3.01 (2.49, 3.63)] and reduce treatment failure [0.29 (0.25, 0.33)] and progressive disease [0.27 (0.22, 0.34)]. It might not increase the risk of adverse drug reactions. For patients with lung cancer, moderate to massive effusion, initial treatment, Karnofsky Performance Status (KPS) score ≥60, or anticipated survival time ≥3 months, Rh-endostatin (30–45 mg each time, once or twice a week 3–4 times) plus DDP (30–60 mg/m2) obtained a significant improvement in clinical response and a reduction of failure and progressive disease. Most results had good robustness and moderate quality. Conclusions Current evidence suggests that Rh-endostatin with DDP may be an optimal combination, which may improve clinical response and reduce failure and progressive disease with good safety. Rh-endostatin (30–40 mg each time, once or twice a week 3–4 times) with DDP (30–40 mg/m2) may be an optimal usage for achieving an ideal response.